A comparative study of proxymetacaine-fluorescein and lignocaine-fluorescein use during applanation tonometry - Birchall, W. (2001)
AIMS—To evaluate the relative merits of proxymetacaine-fluorescein (PROX-FLU) and lignocaine-fluorescein (LIG-FLU) when used to perform applanation tonometry. METHODS—This prospective, masked, double blind study assessed several aspects of the tonometry process—the duration of the stinging sensation and degree of discomfort, the extent of reflex lacrimation induced, the need for subsequent tear film manipulation to ensure an accurate tonometry reading, and total time to complete tonometry—for each preparation. RESULTS—PROX-FLU caused significantly less discomfort and reflex lacrimation than LIG-FLU and accurate tonometry was more rapidly completed when it was used. PROX-FLU was preferred by 98% of the study patients. CONCLUSION—PROX-FLU is a well tolerated and useful alternative to the more widely used LIG-FLU mixture.